Morphophonemic Interference in The Makassar Language in The Use Of Indonesian Language in The Film Area (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the phenomenon of morphophonemic interference from the Makassar language to the use of Indonesian in the film Uang Panai 2. The purpose of this study is to identify and describe the forms of morphophonemic interference found in the film's dialogue. Using a qualitative descriptive approach, this study analyzes the conversation between characters in the film to explore the forms of phoneme substitution, phoneme reduction, and affixation influenced by the Makassar language. The results of the study indicate that the interference affects the structure and pronunciation of Indonesian, reflecting the bilingual character of Makassar speakers and the cultural identity reflected in the use of language in film media. These findings provide a deeper understanding of the phenomenon of linguistic interference in a multimedia context and highlight the role of regional languages ​​in shaping the use of the national language.